Transferrin and Borneol-Enhanced Liposomes for Targeted Rapamycin Delivery in TBI - Cai S; Yuan Z; Chen Y; Gong M; Lai J; Yan P; Mei Z (International Journal of Nanomedicine, 2025)
Shihong Cai,1,2,* Zhongwen Yuan,1,* Yanfang Chen,3 Mingjie Gong,1 Jianqi Lai,1 Pengke Yan,1 Zhengrong Mei1 1Department of Pharmacy, Guangdong Provincial Key Laboratory of Major Obstetric Diseases, Guangdong Provincial Clinical Research Center for Obstetrics and Gynecology, The Third Affiliated Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Zhanjiang Healthcare Security Service Management Center, Zhanjiang, People’s Republic of China; 3Department of Pharmacy, Guangzhou Eighth People’s Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pengke Yan, Email gysyypk@126.com Zhengrong Mei, Email meizhengrong@126.comBackground: The therapeutic potential of rapamycin (RAPA) for traumatic brain injury (TBI) is limited by its low bioavailability and poor penetration across the blood-brain barrier (BBB). We developed transferrin-modified rapamycin and borneol co-delivery liposomes (TF-RAPA/BO-LIP) to overcome these barriers, aiming to enhance both drug delivery to the brain and the treatment efficacy.Methods: We employed the emulsion-solvent evaporation method to prepare TF-RAPA/BO-LIP and characterized their particle size, zeta potential, morphology, stability, and encapsulation efficiency. Pharmacokinetic studies were conducted in SD rats, and drug concentration was analyzed using LC-MS/MS. The brain-targeting capability and therapeutic efficacy were evaluated through in vitro cellular uptake studies, and in vivo in a TBI mouse model using both neurological and cognitive assessments.Results: TF-RAPA/BO-LIP displayed optimal characteristics (95 nm particle size, > 90% encapsulation efficiency) and demonstrated enhanced stability. Pharmacokinetic analyses revealed reduced drug clearance and increased drug concentration-time curve area, indicating improved systemic and brain-specific drug bioavailability. Notably, TF-RAPA/BO-LIP achieved significantly higher RAPA accumulation in the brain tissue. Importantly, treatment with TF-RAPA/BO-LIP significantly ameliorated neurological deficits and improved spatial memory in TBI mice, as evidenced by behavioral tests.Conclusion: Our study highlights TF-RAPA/BO-LIP as a promising strategy for delivering RAPA across the BBB, substantially enhancing its therapeutic efficacy for TBI. This novel liposomal system not only improves RAPA bioavailability but also offers significant neuroprotection, potentially transforming the clinical management of TBI.Keywords: traumatic brain injury, rapamycin, ferroptosis, liposomes